دور الويب 2.0 في زيادة فعالية الضجة التسويقية -دراسة حالة المؤسسة البريطانية Roman Originals- - بريم, ايمان; بوروبي, مصطفى (جامعة الوادي - University of Eloued, 2023)
In this article we will define how information 2.0 can influence decision of custumers to buy goods, so the influence of web information increase custumer’s demand if it will be positif and the opposite will happen if it will be negative opinions. So firm’s profit depends of loyalty of their custumers . Custumers have became the power of any firm, their loyalty has been always the goal for to be competitive in the market, and social media has increase this power and became more and more impressive, and that what a case study of Roman Originals proves . Today no one deny importance of information 2.0, but how we should do it and when, this is the important question
Creating an effective buzz by the web 2.0 -case study of Roman Originals-
مقال
Keywords: الويب 2.0 ; المعلومات 2.0 ; الضجة الالكترونية ; الضجة التسويقية; web 2.0, information2.0, buzz marketing, viral marketing, revenues